Coreferential Devices in the Quranic Interpretation - Muhassin, Mohammad; Hidayati, Dewi Ayu (English Education: Jurnal Tadris Bahasa Inggris, 2019)
This article mainly discusses the coreference in the Quranic interpretation of  Surah Albaqarah by  Abdullah Yusuf Ali. The aims of the research are: to describe and explain the coreference types found in the Quranic interpretation, the  coreference devices, and relationship types of the coreferential devices. The is a kind of descriptive qualitative research. The population consisted 286 interpretation texts of Surah Al-Baqarah with 112 samples taken as the data of the research chosen by using  purposive sampling technique. The result of the research shows that the coreference types found in the Quranic interpretation are: repetition (6,55%), lexical change  (18,03%), substitution (50,81%) and ellipsis (24,59%). Meanwhile,  the coreferential  devices found are: repetition, lexical change,  and  substitution. Finally,  the relationship types of the co-referential devices are anaphoric (88,52%) and cataphoric (11,48%)